2001
DOI: 10.1126/science.1064890
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Dendritic Cell Differentiation by IFN-α in Systemic Lupus Erythematosus

Abstract: Dendritic cells (DCs) are important in regulating both immunity and tolerance. Hence, we hypothesized that systemic lupus erythematosus (SLE), an autoimmune disease characterized by autoreactive B and T cells, may be caused by alterations in the functions of DCs. Consistent with this, monocytes from SLE patients' blood were found to function as antigen-presenting cells, in vitro. Furthermore, serum from SLE patients induced normal monocytes to differentiate into DCs. These DCs could capture antigens from dying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

34
988
4
18

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 1,177 publications
(1,044 citation statements)
references
References 24 publications
34
988
4
18
Order By: Relevance
“…Serum interferon (IFN)-α concentrations are elevated in patients with systemic lupus erythematosus (SLE) [1] and contribute to the break of peripheral tolerance by sustaining the differentiation of myeloid dendritic cells [2]. IFN-α actually increases the differentiation of monocytes into dendritic cells that present antigens from dying cells to CD4 + lymphocytes, resulting in their proliferation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Serum interferon (IFN)-α concentrations are elevated in patients with systemic lupus erythematosus (SLE) [1] and contribute to the break of peripheral tolerance by sustaining the differentiation of myeloid dendritic cells [2]. IFN-α actually increases the differentiation of monocytes into dendritic cells that present antigens from dying cells to CD4 + lymphocytes, resulting in their proliferation.…”
mentioning
confidence: 99%
“…Currently, PDCs activated by DNA- and RNA-containing immune complexes are believed to be the main source of IFN-α in SLE upon triggering of Toll-like receptor (TLR) 9 and TLR7, respectively, in cooperation with CD32 [6-8]. Nevertheless, PDC depletion experiments suggest that other cell types produce IFN-α in SLE [2] and type I IFN production occurs independently of Fcγ receptors in a lupus mouse model [9], indicating that uptake of immune complexes is not required. In a different lupus mouse model, the double-stranded RNA analog poly I:C was shown to induce IFN-α production in spleen monocytes [10], confirming that - depending on the stimulus - cells other than PDCs may produce IFN-α independently of the presence of immune complexes.…”
mentioning
confidence: 99%
“…Second, a clearance deficiency of monocytes and macrophages causes accumulation of apoptotic bodies in different tissue types (20,21). Third, some monocytes become professional antigen-presenting cells upon stimulation with IFN␣ and may present processed antigens of ingested apoptotic cells and nucleosomes to CD4ϩ T cells that subsequently become activated (22).…”
mentioning
confidence: 99%
“…We have previously shown that activation of the dendritic cell system in SLE patients occurs because of an unabated secretion of interferon-␣ (IFN␣) by plasmacytoid dendritic cells (10). In vitro studies also demonstrated that SLE dendritic cells have the unique capacity to activate CD8ϩ T lymphocytes, promoting their differentiation into effector-type cytotoxic T lymphocytes (11), whereas in vivo, there was an increased proportion of cytotoxic T lymphocytes, which correlated with scores on the SLE Disease Activity Index (SLEDAI) (12,13).…”
mentioning
confidence: 99%